PENERAPAN UNSUR TINDAK PIDANA PERBUATAN CURANG DALAM PERIKATAN OLEH PENYIDIK PADA DIREKTORAT RESERSE KRIMINAL UMUM POLDA SUMBAR - Gusman, Fenni (UNES Journal of Swara Justisia, 2020)
The investigation by the West Sumatra Regional Police's Ditreskrimum wascarried out by a contractor who purchased building materials at several shopsand did not pay any payment for the purchase of building materials, thus causingthe loss of building materials shop owners. The application of the elements of thecriminal act of fraudulent acts in the engagement by investigators at the WestSumatra Regional Police's Ditreskrimum consists of subjective and objectiveelements. Subjective elements are people who can be held accountable for theiractions. The presence of "Intent" is an element of error. While the ObjectiveElements. Is an act of buying.Elements as livelihood (beroep) or habit(gewoonte). This means that a livelihood is done only once, but from other thingshe does, it can be concluded that he will do it again and the elements of habit,done more than once. Based on these elements, the main evidence that must beavailable is evidence stating that the act was repeated and there were many ormore than one victim.